Activity dependence of action potential duration in rat supraoptic neurosecretory neurones recorded in vitro. - Bourque, C W (1985)
Action potential durations, measured at one-third peak amplitude, were examined during intracellular recordings in 134 supraoptic nucleus neurones maintained in vitro in perfused hypothalamic explants. Spike durations ranged between 1.2 and 3.9 ms and were dependent on firing frequency. Shortest measurements (1.74 +/- 0.03 ms; mean +/- S.E. of mean) were obtained during relative quiescence, i.e. less than or equal to 0.5 Hz. A gradual increase in firing frequency through continuous injection of depolarizing current prolonged spike duration, with maximum levels (2.68 +/- 0.05 ms) achieved at 20 Hz. When interspike interval variability was eliminated and firing was more precisely regulated by brief 15-20 ms intracellular current pulses given at pre-determined frequencies, a proportional relationship between increasing spike duration and firing frequency was retained but the change in spike duration at frequencies between 2 and 10 Hz was less pronounced. Once action potentials had achieved the long duration configuration, their return to the shorter duration took place gradually during any succeeding silent interval with a time constant of 4.9 s. Action potential broadening occurred progressively and was most pronounced at the onset of spontaneous or current-induced bursts. In thirty-six phasically active neurones, spike broadening at the onset of a burst was concurrent with the presence of 5-10 consecutive short (less than or equal to 100 ms) interspike intervals; thereafter, despite a greater than 50% reduction in firing frequency, action potential durations remained prolonged throughout the burst. In all of nineteen cells tested, frequency-dependent changes in spike duration were reversibly decreased or blocked by Cd2+, Co2+ and Mn2+, or when CaCl2 was exchanged for equimolar amounts of EGTA in the perfusion medium. These observations indicate that a Ca2+ conductance contributes to frequency- and firing-pattern-dependent changes in spike duration in rat supraoptic nucleus neurones.